Erythrodiplax leticia: Description of the female and updated geographic distribution (Odonata: Libellulidae) - Nobre, Carlos Eduardo Beserra (Zootaxa, 2016)
The female of Erythrodiplax leticia Machado is described and illustrated. The geographic distribution of the species is updated, and notes on its natural history are provided.